A Systematic Approach to Identify Biased Agonists of the Apelin Receptor through High-Throughput Screening. (August 2017) - McAnally, Danielle; Siddiquee, Khandaker; Sharir, Haleli; Qi, Feng; Phatak, Sharangdhar; Li, Jian-Liang; Berg, Eric; Fishman, Jordan; Smith, Layton
Biased agonists are defined by their ability to selectively activate distinct signaling pathways of a receptor, and they hold enormous promise for the development of novel drugs that specifically elicit only the desired therapeutic response and avoid potential adverse effects. Unfortunately, most high-throughput screening (HTS) assays are designed to detect signaling of G protein–coupled receptors (GPCRs) downstream of either G protein or β-arrestin–mediated signaling but not both. A comprehensive drug discovery program seeking biased agonists must employ assays that report on the activity of each compound at multiple discrete pathways, particularly for HTS campaigns. Here, we report a systematic approach to the identification of biased agonists of human apelin receptor (APJ). We synthesized 448 modified versions of apelin and screened them against a cascade of cell-based assays, including intracellular cAMP and β-arrestin recruitment to APJ, simultaneously. The screen yielded potent and highly selective APJ agonists. Representative hits displaying preferential signaling via either G-protein or β-arrestin were subjected to a battery of confirmation assays. These biased agonists will be useful as tools to probe the function and pharmacology of APJ and provide proof of concept of our systematic approach to the discovery of biased ligands. This approach is likely universally applicable to the search for biased agonists of GPCRs.